Maturation and germination of oak somatic embryos originated from leaf and stem explants: RAPD markers for genetic analysis of regenerants. (Journal of plant physiology, 2003)
Experiments were performed to determine the influence of maturation medium carbohydrate content on the rates of germination and plantlet conversion (root and shoot growth) of somatic embryos from four embryogenic lines derived from leaf or internode explants of Quercus robur L. seedlings. The conversion rate was favoured by high carbohydrate content as long as the maturation medium contained at least 2% sucrose, which was necessary for healthy embryo development. Given this, sorbitol and mannitol favoured the conversion rate more efficiently than sucrose, the highest rate, 32%, being achieved by medium with 6% sorbitol and 3% sucrose. Maturation treatment did not affect the root or shoot lengths of converted embryos. In supplementary experiments, 2 weeks of gibberellic acid treatment between maturation and germination treatments did not improve germination rates, but did reduce root length and the number of leaves per regenerated plantlet. In the four embryogenic lines tested, plant recovery rate was enhanced by inclusion of benzyladenine into the germination medium following culture of the embryos on maturation medium with 6% sorbitol and 2-3% sucrose. In embryogenic systems it is important to assess the uniformity of the regenerants. Random amplified polymorphic DNA (RAPD) analysis using 32 arbitrary oligonucleotide primers was performed to study variability in DNA sequences within and between four embryogenic lines. No intraclonal nor interclonal polymorphism was detected between embryogenic lines originating from different types of explant from the same seedling, but every one of the primers detected enough polymorphism among clones originating from different plants to allow these three origins to be distinguished. No differences in DNA sequences between regenerated plantlets and their somatic embryos of origin were detected, but a nodular callus line that had lost its embryogenic capacity was found to be mutant with respect to three other clones originating from the same plantlet. This study shows that high carbohydrate levels in the maturation medium significantly increase plant conversion of oak somatic embryos, which exhibit no variation in DNA sequences when proliferated by secondary embryogenesis.